Effects of atrial electromechanical delay and ventriculoatrial conduction over the atrial functions in patients with frequent extrasystole and preserved ejection fraction. Issue 3 (30th January 2019) - Gurbuz, Ahmet Seyfeddin; Ozturk, Semi; Kilicgedik, Alev; Akgun, Taylan; Kalkan, Mehmet Emin; Demir, Serdar; Efe, Suleyman Cagan; Acar, Rezzan Deniz; Akcakoyun, Mustafa; Kirma, Cevat
Abstract: Background: The deterioration of left atrial and ventricular functions was demonstrated in patients with frequent ventricular extrasystole (fVES). The exact pathophysiology of left atrial dysfunction in patients with fVES is unclear. Retrograde ventriculoatrial conduction (VAC) often accompanies fVES, which may contribute to atrial dysfunction. We investigated whether atrial electromechanical delay and VAC are related to these atrial functions in patients with frequent right ventricular outflow tract (RVOT) VES and preserved ejection fraction (pEF). Methods: This study included 21 patients with pEF (eight males, 48 ± 11 years), who had experienced more than 10 000 RVOT‐VES during 24‐h Holter monitoring and had undergone electrophysiological study/ablation. The study also included 20 healthy age‐ and sex‐matched control subjects. Transthoracic echocardiography was performed on all of the subjects. Atrial conduction time was obtained by using tissue Doppler imaging. Strain analysis was performed with two‐dimensional speckle tracking echocardiography. Results: The peak atrial longitudinal strain was significantly impaired in patients with fVES ( P  = 0.01). In addition, although the interatrial and left atrial conduction delay times were significantly different between each group ( P  < 0.001, P  < 0.001), the right atrial conduction delay times were similar. When patients with fVES were divided into groups depending on the existence of retrograde VAC, atrial deformation parameters and conduction delay time did not significantly differ between either group. Conclusion: Frequent RVOT‐VES causes left atrial dysfunction. This information is obtained through strain analyses and recordings of left atrial conduction times in patients with pEF. Regardless, retrograde VAC is not related to atrial dysfunction.